Conventional and Novel Treatment Modalities in Rosacea - Engin B; Özkoca D; Kutlubay Z; Serdaroğlu S (Dove Medical Press, 2020)
Burhan Engin, Defne Özkoca, Zekayi Kutlubay, Server Serdaroğlu Istanbul University-Cerrahpaşa, Cerrahpaşa Medical Faculty, Department of Dermatology and Venerology, İstanbul, TurkeyCorrespondence: Burhan EnginIstanbul University-Cerrahpaşa, Cerrahpaşa Medical Faculty, Department of Dermatology and Venerology, İstanbul 34098, TurkeyEmail burhanengin2000@yahoo.comAbstract: Rosacea is a common skin disease that is troublesome for both the patients and the dermatologists. Erythema, telengiectasia, papulopustular changes and phymatous changes are the main problems faced by the patients and dermatologists in everyday practice. Due to the chronic and relapsing nature of the disease, patients are usually unsatisfied with conventional treatment methods. This article aims at redefining rosacea according to the 2017 consensus and reviewing the different treatment modalities for different manifestations of the disease in depth.Keywords: new, resistant, rosacea, treatment